2022
DOI: 10.3389/fmats.2022.942957
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Hydrogels in Premature Ovarian Failure and Intrauterine Adhesion

Abstract: Premature ovarian failure (POF) and intrauterine adhesion (IUA) that easily lead to reduced fertility in premenopausal women are two difficult diseases to treat in obstetrics and gynecology. Hormone therapy, in vitro fertilization and surgical treatments do not completely restore fertility. The advent of hydrogels offers new hope for the treatment of POF and IUA. Hydrogels are noncytotoxic and biodegradable, and do not cause immune rejection or inflammatory reactions. Drug delivery and stem cell delivery are t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 162 publications
0
2
0
Order By: Relevance
“…Rodent models of PCOS have been widely used [ 81 ], but genomic differences between humans and animals are objective. The use of human-derived cells and biocompatible biomaterials to construct ovarian organoid may provide a new model for the study of the mechanisms of PCOS [ 82 , 83 ].…”
Section: The Role Of Macrophages In Polycystic Ovary Syndrome (Pcos)mentioning
confidence: 99%
“…Rodent models of PCOS have been widely used [ 81 ], but genomic differences between humans and animals are objective. The use of human-derived cells and biocompatible biomaterials to construct ovarian organoid may provide a new model for the study of the mechanisms of PCOS [ 82 , 83 ].…”
Section: The Role Of Macrophages In Polycystic Ovary Syndrome (Pcos)mentioning
confidence: 99%
“…The prevalence of intrauterine adhesions, a troublesome gynecological disease that poses a signicant risk to women's reproductive health, is one of the most pressing issues facing gynecologists today. [1][2][3][4][5] Human amniotic membrane (hAM) is an ideal material with great potential to prevent postoperative adhesion because of its natural biocompatibility and unique properties, such as self-contained stem cells, antibacterial properties, and exibility. Clinical studies have demonstrated that hAM can treat moderate and severe intrauterine adhesions with specic feasibility and safety benets, as the stem cells in hAM could effectively promote the repair of endometriosis.…”
Section: Introductionmentioning
confidence: 99%